TGF-β2 is a Prognostic Biomarker Correlated with Immune Cell Infiltration in Colorectal Cancer: A STROBE-compliant article. Issue 46 (13th November 2020) - Tu, Yifeng; Han, Junjun; Dong, Quanjin; Chai, Rui; Li, Na; Lu, Qiliang; Xiao, Zunqiang; Guo, Yang; Wan, Ziang; Xu, Qiuran
Abstract : Abstract: Transforming growth factor-beta (TGF-β2) is an important cytokine regulating immune cell function. However, whether TGF-β2 controls the invasion of colorectal cancer (CRC) by immune cells is unknown. Therefore, we evaluated the expression of TGF-β2 using multiple databases and determined the relationship between TGF-β2 expression and tumor immune infiltration defined by a set of genetic markers. The analysis demonstrated that the expression of TGF-β2 is closely related to the outcome of many cancers, and this correlation was particularly strong in CRC. In addition, the increased expression of TGF-β2 was significantly associated with the expression of various markers of specific immune cell subpopulations, and overexpression of TGF-β2 was closely related to the prognosis of colon cancer patients. Moreover, TGF-β2 was related to the prognosis and infiltration of the tumor by immune cells in CRC patients. The obtained results indicate that TGF-β2 is a critical factor regulating the recruitment of immune cells and controls their infiltration into colorectal tumors. Thus, high expression of TGF-β2 not only facilitates the prognosis in CRC patients, but also may provide a new target for the treatment of CRC. Abstract : Supplemental Digital Content is available in the text